The Role of Tour Guides in Enhancing Revisit Intentions of Couple Tourists to Bali - I Putu Koisuki Suriana; Lukia Zuraida; Ni Putu Evi Wijayanti (Journal of Applied Sciences in Travel and Hospitality, 2026)
This study examines the role of tour guides in enhancing the intention of couples to revisit Bali, using the framework of experiential marketing theory. The research aims to understand how human-touch elements provided by tour guides influence the travel experience and subsequent revisit intentions of couples visiting Bali. A descriptive, qualitative research design was employed, utilising a purposive sampling technique. Data were collected through in-depth, semi-structured interviews and observations with 16 couples of foreign tourists from diverse countries, including Europe, Asia, Australia, and the United States, aged 24-40 years, who had utilised tour guide services during their visit to Bali. Inductive thematic analysis was conducted using NVivo 12 software to analyse data based on the Experiential Marketing framework, encompassing five dimensions: Sense, Feel, Think, Act, and Relate. The findings reveal that tour guides play multidimensional roles as sensory interpreters, emotional architects, cultural translators, experiential facilitators, and social connectors. Four key functions emerged: facilitators overcoming language and cultural barriers, knowledge transfer agents providing deep destination insights, emotional support providers creating memorable experiences, and social catalysts enhancing security and connectedness. The analysis demonstrates that successful tour guides simultaneously address the sensory, emotional, cognitive, behavioural, and social needs of couple travellers, creating holistic experiences that significantly influence revisit intentions. Human-touch elements remain critical differentiators in tourism experiences, particularly for couples seeking personal and intimate travel encounters that cannot be replicated through digital alternatives. Practically, tourism stakeholders should strengthen tour guide training in emotional intelligence, storytelling, intercultural communication, and personalized service strategies.